A Randomized Trial of Behavioral Nudges Delivered Through Text Messages to Increase Influenza Vaccination Among Patients With an Upcoming Primary Care Visit. Issue 3 (March 2023) - Patel, Mitesh S.; Milkman, Katherine L.; Gandhi, Linnea; Graci, Heather N.; Gromet, Dena; Ho, Hung; Kay, Joseph S.; Lee, Timothy W.; Rothschild, Jake; Akinola, Modupe; Beshears, John; Bogard, Jonathan E.; et al.
Purpose: To evaluate if nudges delivered by text message prior to an upcoming primary care visit can increase influenza vaccination rates. Design: Randomized, controlled trial. Setting: Two health systems in the Northeastern US between September 2020 and March 2021. Subjects: 74, 811 adults. Interventions: Patients in the 19 intervention arms received 1-2 text messages in the 3 days preceding their appointment that varied in their format, interactivity, and content. Measures: Influenza vaccination. Analysis: Intention-to-treat. Results: Participants had a mean (SD) age of 50.7 (16.2) years; 55.8% (41, 771) were female, 70.6% (52, 826) were White, and 19.0% (14, 222) were Black. Among the interventions, 5 of 19 (26.3%) had a significantly greater vaccination rate than control. On average, the 19 interventions increased vaccination relative to control by 1.8 percentage points or 6.1% ( P = .005). The top performing text message described the vaccine to the patient as "reserved for you" and led to a 3.1 percentage point increase (95% CI, 1.3 to 4.9; P < .001) in vaccination relative to control. Three of the top five performing messages described the vaccine as "reserved for you." None of the interventions performed worse than control. Conclusions: Text messages encouraging vaccination and delivered prior to an upcoming appointment significantly increased influenza vaccination rates and could be a scalable approach to increase vaccination more broadly.